2014
DOI: 10.1155/2014/154946
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes in the Response toSalmonella enterica Enteritidis,Salmonella enterica Pullorum, and Poly(I:C) in Chicken Spleen and Caecum

Abstract: Salmonella enterica Enteritidis (S. Enteritidis) and Salmonella enterica Pullorum (S. pullorum) are regarded as a threat to poultry production. This study's aim is to characterize the expression profiles in response to three different challenges and to identify infection-related genes in the chicken spleen and caecum. Groups of the Chinese chicken breed Langshan were challenged with either S. Enteritidis, S. pullorum, or poly(I:C). The concentrations of cytokines and antibodies and the Salmonella colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Here, we identified several significantly enriched GO and KEGG terms involved in organic acid and amino acid metabolism and catalysis after pIC treatment in amphioxus. This was also reported in previous studies, in which the spleen and caecum of Chinese Langshan chickens were challenged by pIC [ 23 ]. Yang et al [ 24 ] reported that hepatitis B virus injection altered expression of lipid metabolism genes in transgenic mice by regulating oxidative stress and interacting with regulatory proteins associated with organic acid metabolism.…”
Section: Discussionsupporting
confidence: 84%
“…Here, we identified several significantly enriched GO and KEGG terms involved in organic acid and amino acid metabolism and catalysis after pIC treatment in amphioxus. This was also reported in previous studies, in which the spleen and caecum of Chinese Langshan chickens were challenged by pIC [ 23 ]. Yang et al [ 24 ] reported that hepatitis B virus injection altered expression of lipid metabolism genes in transgenic mice by regulating oxidative stress and interacting with regulatory proteins associated with organic acid metabolism.…”
Section: Discussionsupporting
confidence: 84%
“…Accumulating literature evidence shows that immune organs play crucial roles in defence against Salmonella infection [32][33][34], and mild zinc alteration dramatically affects the function of immune organs [35]. Therefore, we measured the zinc content in the spleen, thymus and bursa of Fabricius.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that young chickens infected with Salmonella present cachexia, shivering, clustering, head dropping, wing prolapse, loss of appetite, difficulty breathing, loss of body weight, diarrhea, and intestinal lesions from inflammation and damage to villi, leading to high mortality rates (Suzuki, 1994;Ma et al, 2014;Zhou et al, 2014). In our experiment, oral infection with Salmonella was not severe enough to lead to high mortality in the chickens (3.33%), but it did effectively activate the antioxidant system to protect against infection.…”
Section: Discussionmentioning
confidence: 99%